The Effect Of Brand Image And Price On Purchase Interest In Hero 57 Products In Bandung - et. al., Gina Apryani Nurunnisha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the companies engaged in e-cigarettes or e-cigarettes, namely Hero 57 has a good brand image and has an affordable price, but has not been able to increase consumer buying interest, including by having a good brand image and affordable prices so that consumers will arise an interest in making purchases on Hero 57. However, based on graphic data, the distribution of Hero 57 liquid from the distributor to the main reseller has decreased drastically. This research was conducted to obtain the results of a study on the variable brand image, price variable, and purchase interest variable Hero 57 and to analyze how much influence the brand image and price have in determining buying interest in Hero 57. The research method used is descriptive - verification method. The population in this research is consumers who actively use vape but are not interested or have never bought Hero 57 products. A total of 125 samples of respondents are non-probabilty and convenience sampling. Data collection was carried out by means of questionnaires, observations, and interviews to obtain primary data. Statistical data analysis was used using SPSS software. Based on the results of the study, it can be concluded that there is a significant influence between brand image and price variables on purchase intention.